A Study on Suicidal Behavior Among Adolescents in Relation to Depression (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This research delves at the correlation between teenage sadness and suicide thoughts and actions. We surveyed and interviewed distinct groups of teenage using a mixed-methods approach. High levels of depressive symptoms are significantly associated with an increase in suicide inclinations, according to the results. Peer interactions, academic pressure, familial dynamics, and social media all have a role in shaping this relationship. In order to decrease the risk of suicide, the research emphasises the need of early intervention and mental health education. To enhance teenage well-being and create supportive settings, the findings call for community and school-based mental health programmes.